The Effect of Household Detergent Waste on Groundwater Quality - Sulistyaningsih, Dewi; Julia ANGGRAINI; Meyva SALSABILA (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
Domestic detergent waste has become an important concern regarding the environmental impact on groundwater quality. This research aims to investigate the effect of household detergent waste on groundwater quality and efforts to reduce the impact of pollution that can be caused by domestic detergent waste. By using qualitative data methods, this research reveals that domestic detergent waste contains various chemicals that are potentially dangerous and have negative impacts on humans and the environment, which can pollute groundwater and cause household awareness of the household environment. In addition, exposure to residues can cause health problems such as cancer. This research covers various domestic detergent waste processing solutions, including environmentally friendly use and effective waste processing, as well as the role of government in determining groundwater quality parameters. These findings can provide an important contribution to guiding sustainable environmental policies to reduce the negative impacts of domestic detergent waste on groundwater quality